2021
DOI: 10.1177/2325967121992154
|View full text |Cite
|
Sign up to set email alerts
|

Poor Prognostic Factors in Patients With Rotator Cuff Retear

Abstract: Background: The treatment for retears after arthroscopic rotator cuff repair (ARCR) has long been a challenge. Purpose: This study aimed to (1) summarize the characteristics of patients with a retear after primary ARCR and (2) determine the risk factors for poor clinical outcomes after a retear. Study Design: Case-control study; Level of evidence, 3. Methods: We collected the data of patients with a retear after primary ARCR between January 2011 and December 2016. There were 45 patients with retears included (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…On the other hand, numerous studies have investigated independent prognostic factors of postoperative tendon integrity, but the results varied widely across studies, and to date no consensus has been reached except for large tear size. 18,27,32 However, our research showed that postoperative GT coverage was definitely strongly associated with structural integrity regardless of preoperative GT coverage. We also confirmed that the rotator cuff tear with the same preoperative GT coverage could result in better postoperative GT coverage through proper tendon mobilization procedures, and as postoperative GT coverage improved, postoperative structural and clinical outcomes also improved.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…On the other hand, numerous studies have investigated independent prognostic factors of postoperative tendon integrity, but the results varied widely across studies, and to date no consensus has been reached except for large tear size. 18,27,32 However, our research showed that postoperative GT coverage was definitely strongly associated with structural integrity regardless of preoperative GT coverage. We also confirmed that the rotator cuff tear with the same preoperative GT coverage could result in better postoperative GT coverage through proper tendon mobilization procedures, and as postoperative GT coverage improved, postoperative structural and clinical outcomes also improved.…”
Section: Discussionmentioning
confidence: 57%
“…13,22,29 Meanwhile, our study confirmed that only preoperative GT coverage was associated with postoperative GT coverage independently in multivariable analysis. 18,27,32 In other words, anatomic variables or characteristics known to be associated with reparability actually were not associated with postoperative GT coverage independently. Instead, only preoperative GT coverage, in which each of these variables is expressed through complex interrelationships, was independently associated with postoperative GT coverage.…”
Section: Discussionmentioning
confidence: 94%
“…20 It is also argued that successful healing of the rotator cuff tendon does not correlate with clinical improvement of symptoms or patient satisfaction. 15 The negative effect of a retear on outcome was inconsistent across the various functional scores in our review and…”
Section: Discussionmentioning
confidence: 72%
“…The mean age was 56.3 years (range, 25-77) and the mean follow-up was 14.0 years (range, 9-20). Five studies 12,21,[31][32][33] reported on aRCR outcomes while 6 studies provided outcomes after open 3,23 or mini-open 1,5,7,23,36 rotator cuff repairs ( [10][11][12][13][14][15][16][17][18][19][20]. There were no significant demographical differences between the groups (P = .886).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Lee et al 30 revealed that the possibility of revision surgery was higher in patients who had relative changes in the AP tear size of >14.6% compared with patients who did not require revision surgery. According to Kim et al, 22 revision surgery should be considered in female patients or those who smoke with poor clinical outcomes and a larger retear than the preoperative tear size.…”
Section: Discussionmentioning
confidence: 99%